2010
DOI: 10.1111/j.1365-2702.2010.03410.x
|View full text |Cite
|
Sign up to set email alerts
|

The handling of peripheral venous catheters – from non‐compliance to evidence‐based needs

Abstract: National guidelines should be based on evidence and current facts, and evaluation of guidelines should be given priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
0
6
1
8
Order By: Relevance
“…Moreover, the present study does not provide a definition of thrombophlebitis, rendering comparisons with other similar studies difficult. Although we agree with Hasselberg et al (2010) that national guidelines should be based on evidence, the fact remains that their study does not contribute solid evidence for replacement times of in situ PVCs. It is essential to use the concept of evidence correctly, especially when we raise arguments concerning cost effectiveness, better use of nurses' time, and saving patients from unnecessary suffering.…”
mentioning
confidence: 51%
See 3 more Smart Citations
“…Moreover, the present study does not provide a definition of thrombophlebitis, rendering comparisons with other similar studies difficult. Although we agree with Hasselberg et al (2010) that national guidelines should be based on evidence, the fact remains that their study does not contribute solid evidence for replacement times of in situ PVCs. It is essential to use the concept of evidence correctly, especially when we raise arguments concerning cost effectiveness, better use of nurses' time, and saving patients from unnecessary suffering.…”
mentioning
confidence: 51%
“…Professional staff were instructed to complete the registry correctly, for example, thrombophlebitis. Concerning relevance to clinical practice, Hasselberg et al (2010) suggest that the findings could be easily implemented in clinical practice by revising the Swedish national guideline that PVCs should be removed every 12-24 hours to avoid complications, and instead recommend every 72 hours, as shown by the present study.…”
Section: Ewa Idvall Christel Bahtsevani and Lena Gunningbergmentioning
confidence: 69%
See 2 more Smart Citations
“…(12) In this research, no significant difference was found between the variables analyzed for obstruction, but a study involving surgical patients appointed that the 22 gauge caliber, used in 8.1% of the participants, presented more cases of obstruction, with a proven statistical difference (p=0.0004). (25) Equivalent rates resulted in 10% (9) (n=11 out of 110 catheters) and in 11.7% (12) for obstruction or function loss. For traction, similar to the present findings, studies measure rates of 10.2%, (4) 7.8%, (24) and between 6 and 9%.…”
Section: Discussionmentioning
confidence: 99%